Changes in neutral genetic variability of the isolated brown bear (Ursus arctos) population of Trentino (Italy) two decades after its reintroduction - Marinangeli, L.; Rossi, C.; Crestanello, B.; Pedrotti, L.; Groff, C.; Mucci, N.; Davoli, F.; Nonnis Marzano, F.; Hauffe, H. C. (country:IT, 2022)
The current population of brown bear (Ursus arctos) in Trentino is the result of a reintroduction which aimed at rescuing autochthonous individuals from the near extinction. Between 1999 and 2002, 10 bears were trapped in neighbouring Slovenia and released in Trentino. Since then, the population has increased faster than expected, but remained isolated in a small geographical area. The population has been monitored genetically since 2003, and a study by de Barba et al. (2010), using non-invasive samples collected in 2002-2008 and 10 microsatellite (STR) loci, found a significant decrease in expected heterozygosity (He) and allelic richness (A) compared to founders. Here, we studied the genetic variation of the same population for a longer time period analysing the 174 genotypes at 15 STR loci observed until 2019. Changes in diversity indices were estimated according to different subdivisions of the population based on: 1. Year (considering both 15 and 10 STR loci in order to compare the two studies). 2. Generation (founder population F0, first generation F1, etc.) 3. Cohort (individuals born in the same 5-year period, the generation time calculated for this species). 4. Group (30 randomly-chosen individuals from 3-year periods to test if standard population genetic studies would accurately estimate genetic diversity). All the subdivision strategies showed an early increase in diversity indices He and A, followed by a rapid reduction through time and a stabilization of the values in recent years; trend more significant for 15 than 10 STR. Interestingly, levels of inbreeding (Fis) increased, but not as dramatically as expected, given the small number of founders and males which contributed to the gene pool. Simulations indicate that genetic diversity will continue to decrease, although management strategies such as exchanging individuals with or a new reintroduction of few individuals from Slovenia could reverse the trend. These results underline the importance of costantly monitoring small reintroduced ...